2016
DOI: 10.1515/chempap-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of PCB-contaminated sediments and evaluation of their pre- and post-treatment ecotoxicity

Abstract: The paper deals with the application of two perspective and promising bioremediation approaches, bioaugmentation and biostimulation, applied to sediment contaminated with polychlorinated biphenyls (PCBs) with the aim to enhance biodegradation of PCBs. Sediments were sampled from Strážsky canal, an industrial waste canal that flows from a former PCB-factory through the Laborec river into the Zemplínska šírava water reservoir, all located in the eastern part of Slovakia. Bioaugmentation of sediments was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This situation usually leads to higher toxicity of the environment. Therefore, the microorganisms able only to modify toxic compounds probably cooperate with other organisms to achieve complete mineralization of contaminants into CO 2 and H 2 O or at least transform the parent compounds into less or nontoxic intermediates [76].…”
Section: The Presence Of Terpene-containing Plant Matrices Protected mentioning
confidence: 99%
“…This situation usually leads to higher toxicity of the environment. Therefore, the microorganisms able only to modify toxic compounds probably cooperate with other organisms to achieve complete mineralization of contaminants into CO 2 and H 2 O or at least transform the parent compounds into less or nontoxic intermediates [76].…”
Section: The Presence Of Terpene-containing Plant Matrices Protected mentioning
confidence: 99%
“…In Lizano-Fallas et al (2017), for example, the ecotoxicity test with Daphnia magna 585 showed clear detoxification, whilst the detoxification patterns remain unclear when applying the 586 phytotoxicity test. Ecotoxicological tests can also be used to determine the most suitable 587 bioremediation technique in a given case, as reported in Dudášová et al (2016).…”
mentioning
confidence: 99%